N-acetylglucosamine-phosphatidylinositol de-N-acetylase as a novel target for probing potential inhibitor against Leishmania donovani. Issue 5 (24th March 2023) - Kumar, Mukesh; Tripathi, Manish Kumar; Gupta, Deepali; Kumar, Sanjit; Biswas, Nihar Ranjan; Ethayathulla, A. S.; Kaur, Punit
Abstract: Leishmania donavani is the causative agent of leishmaniasis, responsible for social and economic disruption, especially in developing countries. Lack of effective drugs with few side effects have necessitated the discovery of newer therapeutic solutions for leishmaniasis. Glycophosphatidylinositol (GPI) synthesis plays a vital role in protozoan cell membranes structural formation and antigenic modification. Hence, any disruption in its biosynthesis can prove fatal to the parasitic protozoans. N-acetylglucosamine-phosphatidylinositol de-N-acetylase (NAGP-deacetylase) is an enzyme from the GPI biosynthetic pathway that catalyzes the deacetylation of N-acetylglucosaminylphosphatidylinositol to glucosaminylphosphatidylinositol, a step essential for the proper functioning of the enzyme. In the quest for novel scaffolds as anti-leishmaniasis agents, we have executed in silico virtual screening, density function theory, molecular dynamics and MM-GBSA based energy calculations with a natural product library and a diverse library set from Chembridge database. Two compounds, 14671 and 4610, were identified at the enzyme's active site and interacted with catalytic residues, Asp43, Asp44, His41, His147, His 150, Arg80 and Arg231. Both molecules exhibited stable conformation in their protein-ligand complexes with binding free energies for compound-14671 and compound-4610 of −54 ± 4 and −50 ± 4 kcal/mol, respectively. These scaffolds can be incorporated in future synthetic determinations, focusing on developing druggable inhibitor support, increasing potency, and introducing species selectivity. Communicated by Ramaswamy H. Sarma